The transnational hybridisation of Mozambican nature. Issue 2 (3rd April 2017) - Diallo, Rozenn N.; Rodary, Estienne
ABSTRACT: This article looks at the relations between Mozambique and transnational dynamics in nature conservation, and the consequences in terms of identity and practice. More specifically, it focuses on Mozambican nature as a political construct, its evolution over time since the independence of Mozambique in 1975, its management during the war and its (re)creation into 'pristine' areas after 1992, which facilitated new forms of inclusion in transnational networks and of disjunction at national level. We argue that the shift from relative isolation to inclusion in transnational networks (both regional – particularly South African – and global) brought new ways to deal with nature. In particular, it has radically transformed what was conceived as 'nature' and thus what was worth protecting, managing and controlling.